Asynclitism: a literature review of an often forgotten clinical condition. (2nd November 2015) - Malvasi, Antonio; Barbera, Antonio; Di Vagno, Giovanni; Gimovsky, Alexis; Berghella, Vincenzo; Ghi, Tullio; Di Renzo, Gian Carlo; Tinelli, Andrea
Abstract: Asynclitism is defined as the "oblique malpresentation of the fetal head in labor". Asynclitism is a clinical diagnosis that may be difficult to make; it may be found during vaginal examination. It is significant because it may cause failure of progress operative or cesarean delivery. We reviewed all literature for asynclitism by performing an extensive electronic search of studies from 1959 to 2013. All studies were first reviewed by a single author and discussed with co-authors. The following studies were identified: 8 book chapters, 14 studies on asynclitism alone and 10 papers on both fetal occiput posterior position and asynclitism. The fetal head in a laboring patient may be associated with some degree of asynclitism; this is seen as usual way of the fetal head to adjust to maternal pelvic diameters. However, marked asynclitism is often detected in presence of a co-existing fetal head malposition, especially the transverse and occipital posterior positions. Digital diagnosis of asynclitism is enhanced by intrapartum ultrasound with transabdominal or transperineal approach. The accurate diagnosis of asynclitism, in an objective way, may provide a better assessment of the fetal head position that will help in the correct application of vacuum and forceps, allowing the prevention of unnecessary cesarean deliveries.